Metal and dust exposure in workers from the metal recycling industry in Sweden: cross-sectional GreenMetalWaste study - Anja Stajnko; Michael Levi; Malin Engfeldt; Robert Linder; Mats Leeman; Else Åkerberg Krook; Eva Assarsson; Henrik Enquist; Camilla Dahlqvist; Åsa Ek; Karin Lovén; Theo Bodin; et al. (International Journal of Hygiene and Environmental Health, 2026)

Hexavalent chromium still a concern in Sweden – Evidence from a cross-sectional study within the SafeChrom project - Zheshun Jiang; Linda Schenk; Eva Assarsson; Maria Albin; Helen Bertilsson; Eva Dock; Jessika Hagberg; Lovisa E. Karlsson; Pete Kines; Annette M. Krais; Stefan Ljunggren; Thomas Lundh; et al. (International Journal of Hygiene and Environmental Health, 2024)

Underground emissions and miners’ personal exposure to diesel and renewable diesel exhaust in a Swedish iron ore mine - Louise Gren; Annette M. Krais; Eva Assarsson; Karin Broberg; Malin Engfeldt; Christian Lindh; Bo Strandberg; Joakim Pagels; Maria Hedmer (International Archives of Occupational and Environmental Health, 2022)
Purpose Underground diesel exhaust exposure is an occupational health risk. It is not known how recent intensified emission legislation and use of renewable fuels have reduced or altered occupational exposures. We characterized these effects on multipollutant personal exposure to diesel exhaust and underground ambient air concentrations in an underground iron ore mine. Methods Full-shift personal sampling (12 workers) of elemental carbon (EC), nitrogen dioxide (NO 2 ), polycyclic aromatic hydrocarbons (PAHs), and equivalent black carbon (eBC) was performed. The study used and validated eBC as an online proxy for occupational exposure to EC. Ambient air sampling of these pollutants and particle number size distribution and concentration were performed in the vicinity of the workers. Urine samples (27 workers) were collected after 8 h exposure and analyzed for PAH metabolites and effect biomarkers (8-oxodG for DNA oxidative damage, 4-HNE-MA for lipid peroxidation, 3-HPMA for acrolein). Results The personal exposures (geometric mean; GM) of the participating miners were 7 µg EC m −3 and 153 µg NO 2 m −3 , which are below the EU occupational exposure limits. However, exposures up to 94 µg EC m −3 and 1200 µg NO 2 m −3 were observed. There was a tendency that the operators of vehicles complying with sharpened emission legislation had lower exposure of EC. eBC and NO 2 correlated with EC, R = 0.94 and R = 0.66, respectively. No correlation was found between EC and the sum of 16 priority PAHs (GM 1790 ng m −3 ). Ratios between personal exposures and ambient concentrations were similar and close to 1 for EC and NO 2 , but significantly higher for PAHs. Semi-volatile PAHs may not be effectively reduced by the aftertreatment systems, and ambient area sampling did not predict the personal airborne PAHs exposure well, neither did the slightly elevated concentration of urinary PAH metabolites correlate with airborne PAH exposure. Conclusion Miners’ exposures to EC and NO 2 were lower than those in older studies indicating the effect of sharpened emission legislation and new technologies. Using modern vehicles with diesel particulate filter (DPF) may have contributed to the lower ambient underground PM concentration and exposures. The semi-volatile behavior of the PAHs might have led to inefficient removal in the engines aftertreatment systems and delayed removal by the workplace ventilation system due to partitioning to indoor surfaces. The results indicate that secondary emissions can be an important source of gaseous PAH exposure in the mine.

Mild steel welding is associated with alterations in circulating levels of cancer-related proteins - Anda R. Gliga; Tahir Taj; Maria Hedmer; Eva Assarsson; Lars Rylander; Maria Albin; Karin Broberg (Archives of Toxicology, 2019)
Welding fumes were recently classified as carcinogenic to humans and worldwide millions work as welders or perform welding operations. The purpose of this study was to identify new biomarkers of welding-induced carcinogenesis. We evaluated a panel of 91 putative cancer-related proteins in serum in a cohort of welders working with mild steel ( n = 77) and controls ( n = 94) from southern Sweden sampled on two occasions 6-year apart using a longitudinal analysis (linear mixed models). The significant results from the longitudinal analysis were tested for reproducibility in welders ( n = 88) and controls ( n = 69) sampled once during the same sampling period as timepoint 1 or timepoint 2 (linear regression models), i.e., in a cross-sectional setting. The models were adjusted for age, body-mass index, and use of snus. All study participants were non-smokers at recruitment. Exposure to welding fumes was assessed using questionnaires and respirable dust measurement in the breathing zone that was adjusted for personal respiratory protection equipment. The median respirable dust in welders was 0.7 (0.2–4.2) and 0.5 (0.1–1.9) mg/m 3 at the first and second timepoints, respectively. We identified 14 cancer-related proteins that were differentially expressed in welders versus controls in the longitudinal analysis, out of which three were also differentially expressed in the cross-sectional analysis (cross-sectional group). Namely, syndecan 1 (SDC1), folate receptor 1 (FOLR1), and secreted protein acidic and cysteine rich (SPARC) were downregulated, in welders compared with controls. In addition, FOLR1 was negatively associated with years welding. Disease and function analysis indicated that the top proteins are related to lung cancer as well as cell invasion and migration. Our study indicates that moderate exposure to welding fumes is associated with changes in circulating levels of putative cancer-related proteins, out of which FOLR1 showed a clear dose–response relationship. It is, however, unclear to which extent these changes are adaptive or potential early biomarkers of cancer.

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)